Implementation of Increased Education Participation in the Pandemic Era Through the Conditional Cash Transfer - Bayu Priambodo (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
The problem of education in Indonesia is still experiencing many problems, especially at the primary and secondary education levels. This can be seen in several cases of children dropping out of school, one of which occurred in Ponorogo Regency. For this reason, this study aims to describe the implementation of increasing educational participation through the Conditional Cash Transfer Program. This study uses descriptive qualitative methods and data searches using interviews. The results of this study indicate that the implementation of the Conditional Cash Transfer Program has been carried out according to the procedure. However, the level of education participation is still not optimal because children still do not continue their education to the next level. For this reason, cooperation from various parties is needed to increase the level of education participation in the Ponorogo Regency.